Pulmonary and extrapulmonary tuberculosis, an inflammatory disease misdiagnosed as cancer - Gheryani, Nabeia (International Journal of Medical Research and Review, 2024)
Introduction: tuberculosis is a serious infection associated with high mortally rate if not treated. The clinical and imaging presentation are usually nonspecific and can mimic malignancy; therefore, extrapulmonary TB should be considered in the differential diagnosis of any suspicious extrapulmonary masses, particularly in immunocompromised patients. Objective: the aim of this study is to analyzed 160 case of pulmonary and extra-pulmonary tuberculosis and correlate the pathological features with the clinical data and to find the most common differentiation diagnosis of both pulmonary and extrapulmonary tuberculosis Methodology: a retrospective analysis of 160 case of pulmonary and extra-pulmonary tuberculosis was performed. The age, the gender, the site, and the symptoms of the lesion were collected, extrapulmonary sites were detected including rare and unusual sites and the differential diagnosis of these lesion was highlighted. The data were plotted in graphs and were analyzed Result: in our study 63.6% were male and 36.4 were females. Majority of the patients were in the age group of 21-30 years followed by 31- 40-year, cough and hemoptysis were the most common symptoms followed by cervical swelling with 39% and 33% respectively. The most common sites were lung with (39%) and cervical swelling with (33%). The main differential diagnosis for many pulmonary and all extra-pulmonary tuberculosis was malignancy Conclusion: tuberculosis is a serious young person disease that can affect almost every organ and tissue of the body and should be considered in the differential diagnosis of suspicious masses, as tuberculosis often misdiagnosed as cancer keywords: Mycobacterium tuberculosis, cancer, malignancy, extrapulmonary.